Leaching and recycling of NdFeB permanent magnets using ionic non-toxic hydrotropes instead of extractants - El Maangar, Asmae; Fleury, Clément; Pellet-Rostaing, Stéphane; Zemb, Thomas (Frontiers in Chemical Engineering, 2024)
We show hereby that recycling of NdFeB permanent magnets by selective leaching and precipitation is possible, using an electrolyte as hydrotrope, thus avoiding the need of any specific extractant molecules. We analyse the yield of the extractant-free process and show that the non toxic formulation of Sodium Salicylate and ethylacetate used as diluent and choosing the optimal tie-line in a ternary phase diagram allows extraction using any type of acid in the aqueous phase. Iron is well separated from rare earths and the product can be recovered directly form the fluid used in separation by oxalic acid precipitation.